THE APPLICATION OF RESTORATIVE JUSTICE AS A NEW PARADIGM OF PUNISHMENT IN THE NEW CRIMINAL CODE (LAW NO. 1 OF 2023) IN MISDEMEANOR CRIMES - Fadilah Agustin; Ammelya Vega (Fakultas Hukum Universitas Swadaya Gunung Jati, 2026)
Restorative justice is a new paradigm in the Indonesian criminal justice system, which strives to restore social bonds, protect victims, rehabilitate offenders, and establish balance in society. This idea emerged as a critique of the retributive approach, which was focused on punishing the offender. This study aims to assess the restorative justice arrangements contained in the New Criminal Code (Law Number 1 of 2023), to analyze the application of these arrangements based on the theories of the purpose of punishment and justice, and to determine the obstacles to the implementation of these arrangements in the Indonesian criminal law system. The research method used is doctrinal with a regulatory and conceptual approach. Legal resources are collected from literature assessments of pertinent laws and regulations, publications and scientific journals. The results of the study show that Restorative Justice has obtained normative legitimacy through different rules such as Police guidelines, Prosecutor's Regulations, and Supreme Court Regulations. Restorative justice is more broadly controlled under the New Criminal Code. Restorative justice under the New Criminal Code is a blended theory (retributive-teleological theory). It blends punishment with the social aim of criminalization by regulating social work crimes, supervision crimes, ultimum remedium and judicial pardon. Furthermore, the idea of restorative justice is connected with the theory of justice by John Rawls in the sense that it stresses the restoration of the rights of victims, the culpability of the offender, and the role of the community in dealing with criminal cases. However, the implementation of this policy still has various challenges, including imbalance in the positions of victims and perpetrators, lack of awareness among law enforcement officials, and uneven implementation throughout regions.